Juvenile justice redeeming our children - Krisberg, Barry (Sage Publications, 2005)
Juvenile Justice: Redeeming Our Children debunks myths about juvenile justice in order to achieve an ideal system that would protect vulnerable children and help build safer communities. Author Barry Krisberg assembles broad and up-to-date research, statistical data, and theories on the U.S. juvenile justice system to encourage effective responses to youth crime. This text gives a historical context to the ongoing quest for the juvenile justice ideal and examines how the current system of laws, policies, and practices came into place." "Juvenile Justice reviews the best research-based knowledge on what works and what does not work in the current system. The book also examines failed juvenile justice policies and applies high standards of scientific evidence to seek new resolutions. This text helps students embrace the value of redemptive justice and serves as a springboard for the current generation to implement sounder social policies." "Juvenile Justice is an ideal textbook for undergraduate and graduate students studying juvenile justice in Criminology, Criminal Justice, and Sociology. The book is also an excellent supplemental text for juvenile delinquency courses.--Jacket.